2012
DOI: 10.1074/jbc.m112.344176
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated Regulation of Transcription Factor Bcl11b Activity in Thymocytes by the Mitogen-activated Protein Kinase (MAPK) Pathways and Protein Sumoylation

Abstract: Background:The transcription factor Bcl11b plays essential roles during T-cell development. Results: Bcl11b activity in thymocytes is regulated by MAPK-mediated phosphorylation and subsequent sumoylation and ubiquitination. Conclusion: A regulatory pathway links thymocyte stimulation, MAPK activation, and Bcl11b-dependent regulation of gene expression during late T-cell development. Significance: This work has implications for the role of Bcl11b in T-cell development and leukemogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(82 citation statements)
references
References 71 publications
3
78
0
1
Order By: Relevance
“…Mutated in many T-cell acute lymphoblastic leukemias. [63][64][65] LOC100506088 Uncharacterized 2p21 cDNA discovered in a pulmonary carcinoid tumor; function unknown. Neuroendocrine tumor 92-gene classifier…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutated in many T-cell acute lymphoblastic leukemias. [63][64][65] LOC100506088 Uncharacterized 2p21 cDNA discovered in a pulmonary carcinoid tumor; function unknown. Neuroendocrine tumor 92-gene classifier…”
Section: Discussionmentioning
confidence: 99%
“…These genes are described in more detail in Table 6 [63][64][65] and LOC100506088 (uncharacterized). To visualize how well these 15 genes can distinguish neuroendocrine subtypes in the validation cohort, PCA were performed and the first three principal components were used to produce a three-dimensional plot showing the unsupervised clustering pattern of the different neuroendocrine subtypes (Figure 4).…”
Section: Exploratory Analysis Of Neuroendocrine Gene Subsetsmentioning
confidence: 99%
“…Okadaic acid and calyculin A were dissolved in dimethyl sulfoxide (DMSO) and used at a final concentration of 1 M and 50 nM, respectively. Calyculin A also inhibits arsenicinduced PML (promyelocytic leukemia protein) SUMOylation (30) and BCL11B SUMOylation (21,31). The SUMOylation inhibitors 2-D08 [2=,3=,4=-trihydroxy-flavone, 2-(2,3,4-trihydroxyphenyl)-4H-1-benzopyran-4-one], which is specific and blocks SUMO (small ubiquitinlike modifier) transfer from the Ubc9-thioester complex to the substrates (32), and anacardic acid, which blocks SUMOylation without affecting ubiquitination (33), were both obtained from Sigma and used at a final concentration of 50 M (34).…”
Section: Methodsmentioning
confidence: 99%
“…This dual behavior of BCL11B as a transcriptional repressor and activator is not fully understood but clearly relies on a dynamic cross talk between BCL11B PTMs. Indeed, mass spectrometry analyses of thymocytes isolated from 4-to 8-week-old mice and stimulated with a mixture of phorbol ester and calcium ionophore used as an in vitro model mimicking T-cell receptor (TCR) activation identified several mitogen-activated protein kinase (MAPK) phosphorylation sites of BCL11B and confirmed its SUMOylation on lysine 679 (21). These phosphorylation events then initiate a rapid and complex cycle of BCL11B PTMs including deSUMOylation, rephosphorylation, and reSUMOylation, allowing recruitment of the transcriptional coactivator P300 to activate Id2 transcription (21,22).…”
mentioning
confidence: 99%
“…SUMO-targeted ubiquitin ligases (STUbL proteins) recognize SUMOylated substrates, and catalyze the desumoylation and ubiquitination of these substrates, the latter of which may target the protein for degradation via the proteasomal pathway. A recent study has reported Ctip2 SUMOylation and ubiquitination in thymocytes (Zhang et al, 2012). In addition, ubiquitination and proteosomal degradation of anti-apoptotic Bcl2 protein has been observed in human dermal papilla cells and in keratinocytes (Luanpitpong et al, 2012;Luanpitpong et al, 2011).…”
Section: Ctip2 Expression Is Regulated By Egf-egfr Signaling In Prolimentioning
confidence: 96%